A multi-scale homogenization approach for the effective thermal conductivity of dry lime–hemp concrete. Issue 2 (4th March 2018) - Nguyen-Sy, T.; Tran-Le, A.D.; Nguyen-Thoi, T.; Langlet, T.
Abstract : Lime–hemp concrete is an environmentally friendly material that is used more and more in building construction. This study develops a multi-scale homogenization approach to model the effective thermal conductivity of this bio-based material. The developed model dedicated to non-compacted and compacted hemp concrete takes into account the shape and the orientations of pores of hemp particles as well as imperfect particle-binding interfaces. Unknown properties of the solid phase of hemp particles and binding, and that of the particle-binding interface are calibrated by inverse analysis using available experimental data. The model is then used to carry out a sensitivity analysis to study the effect of the porosities of hemp particles and binding, the volume fraction of hemp particles, density and temperature on the overall thermal conductivity of hemp concrete. Analytical solution proposed can be used for a fast estimation and optimization of the thermal conductivity of hemp concrete, which is very useful for the building design.